2014
DOI: 10.1007/s13258-014-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequence analysis from multiple gene fragments reveals genetic heterogeneity of Crassostrea ariakensis in East Asia

Abstract: The native Asian oyster, Crassostrea ariakensis is one of the most common and important Crassostrea species that occur naturally along the coast of East Asia. Molecular species diagnosis is a prerequisite for population genetic analysis of wild oyster populations because oyster species cannot be discriminated reliably using external morphological characters alone due to character ambiguity. To date there have been few phylogeographic studies of natural edible oyster populations in East Asia, in particular this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
5
10
0
Order By: Relevance
“…This method is easy to visualize and can be extensively applied to studies of genetic diversity in C. ariakensis. Our findings were consistent with those of previous molecular taxonomic studies which found that C. ariakensis from northern China, Korea, and Japan were more closely related, but did not share a common haplotype with the southern populations using polymorphic microsatellite markers, mitochondrial COI and 16S rRNA sequence variation, and nuclear ITS-1 locus (Wang et al, 2004;Zhang et al, 2005;Xiao et al, 2010;Kim et al, 2014). The molecular data indicate that biogeographic barriers, such as the Yangtze River estuary, exist and isolate the northern and southern C. ariakensis populations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This method is easy to visualize and can be extensively applied to studies of genetic diversity in C. ariakensis. Our findings were consistent with those of previous molecular taxonomic studies which found that C. ariakensis from northern China, Korea, and Japan were more closely related, but did not share a common haplotype with the southern populations using polymorphic microsatellite markers, mitochondrial COI and 16S rRNA sequence variation, and nuclear ITS-1 locus (Wang et al, 2004;Zhang et al, 2005;Xiao et al, 2010;Kim et al, 2014). The molecular data indicate that biogeographic barriers, such as the Yangtze River estuary, exist and isolate the northern and southern C. ariakensis populations.…”
Section: Discussionsupporting
confidence: 91%
“…Oysters from the northern estuaries cannot survive in southern environments, and the survival, metabolic rate, and growth for both populations showed greater performance in their native habitats than in their translocated non-native habitats. These findings provide critical evidence for adaptive divergence between the northern and southern C. ariakensis in China, which supports previous observations of their differentiation using limited neutral markers (Wang et al, 2004;Zhang et al, 2005;Xiao et al, 2010;Kim et al, 2014). Adaptive divergence in these fitness-related traits as well as in physiological and molecular parameters was also found in two congeneric oyster species, C. gigas and C. angulata, which are naturally distributed along the northern and southern coasts of the Yangtze River, respectively (Wang et al, 2010;Beck et al, 2011), using the same experimental approaches by combining common garden and reciprocal transplantation (Li et al, 2017.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The level of genetic diversity of C. gigas was characterized by moderate haplotype diversity (4 of 12 populations had low values, including LZ, PL, ZS and SU) and low nucleotide diversity, which was partly consistent with the previous conclusions reported by Sekino et al [52]. In addition, the level of genetic variation for C. gigas was relatively lower than that of some co-distributed bivalves (Table 5), such as C. sinensis [13], Tegillarca granosa [14], Crassostrea ariakensis [53] and Atrina pectinate [21]. A different population history of these species was assumed to be responsible for the differences in genetic variations.…”
Section: Population Genetic Diversitysupporting
confidence: 89%
“…For several decades, mitochondrial DNA (mtDNA) and microsatellite genetic markers have been the most common types used for molecular ecological studies (Beheregaray, 2008;Kim et al, 2014). In recent years, however, with the rapid increase in the availability of genomic information on oysters from expressed sequence tag (EST) collections, EST-derived simple sequence repeats (SSRs) and single nucleotide polymorphisms (SNPs), a genomic approach to molecular marker development has become an attractive alternative to complement-existing markers because then can reduce time and cost compared with development of traditional genomic libraries.…”
Section: Introductionmentioning
confidence: 99%